Kohabitasi Dalam Perspektif Hukum Pidana, dan Hak Asasi Manusia: Antara Realitas dan Norma Sosial - Emirza Nur Wicaksono (Journal of Law Perspectives Review, 2025)
The phenomenon of cohabitation as a form of living together without a legally recognized marriage has become increasingly prominent within Indonesian social dynamics, yet its existence is confronted with criminalization through the provisions of Law Number 1 of 2023 concerning the Criminal Code (KUHP). This study aims to analyze the regulation of cohabitation in the new Criminal Code, assess its compatibility with human rights principles as stipulated in Law Number 39 of 1999 on Human Rights, and understand the influence of social norms in its implementation. Using a normative juridical method with statutory and conceptual approaches, this research examines the tension between public morality, social reality, and the protection of individual rights. The findings show that the criminal provisions on cohabitation in the KUHP are moralistic in nature and not fully aligned with human rights principles, particularly those related to privacy, personal freedom, proportionality, and non-discrimination. Its application in society is also heavily influenced by diverse social norms, creating the potential for selective criminalization. This study concludes that the formulation of Indonesian criminal law needs to be directed toward a more humanistic and human rights-oriented approach, positioning criminal law as ultima ratio and avoiding disproportionate intervention in the private sphere of citizens.